Grounding Islamic Religious Education in Contemporary Social Reality - lutfi firdausi; Rohmatul Faizah; Muh. Ibnu sholeh; Siti Fatinnah binti Ab Rahman (International Journal of Education and Learning, 2026)
The main problem in this research is how to strengthen the implementation of Islamic Religious Education so that it remains relevant and is able to shape the moral character and social concern of students amidst contemporary social changes influenced by globalization and digitalization. This study aims to analyze strategies for grounding Islamic Religious Education within social realities through a conceptual approach oriented toward integrating religious values with community life practices. The research employs a qualitative approach using a library research design that draws upon various scholarly sources, including books, journal articles, and relevant academic documents. Data were collected through documentation techniques and analyzed using descriptive-analytical methods involving data reduction, data presentation, and conceptual interpretation. The findings indicate that the implementation of Islamic Religious Education can be strengthened through contextualizing learning materials, reinforcing reflective-dialogical approaches, integrating digital and social literacy, applying social experience–based learning, promoting educators’ role modeling, strengthening universal humanitarian values, and implementing practice-based social evaluation. These strategies enable religious education to be understood not merely as the transfer of normative knowledge, but as a process of value internalization that influences social behavior. This study underscores the importance of developing adaptive, humanistic, and socially relevant approaches to religious education in response to modern societal developments.